Adrenal Cavernous Hemangioma: A Rarely Perceived Pathology—Case Illustration and Review of Literature - Jad A. Degheili; Nassib F. Abou Heidar; Mouhammad El-Moussawi; Ayman Tawil; Rami W. Nasr (Case Reports in Pathology)
Cavernous hemangiomas are endothelial tumors that rarely affect the adrenal glands. Most of these tumors remain silent and are incidentally found on abdominal imaging. Hardly ever, these tumors are endocrinologically functional. They may present as vague abdominal pain. Surgical resection remains the mainstay for large masses. In this paper, we are presenting a case of adrenal cavernous hemangioma in a 83-year-old male patient who initially presented for workup of vague abdominal and bilateral flank pain. A computed tomography scan of the abdomen showed an 8 cm right adrenal adenoma which was metabolically nonfunctional. The mass was completely resected through an open subcostal incision, with no encountered postoperative complications. A highlight of all published cases of adrenal hemangiomas since 1955 is also presented and reviewed.